Menanamkan Kecintaan Anak terhadap Al-Quran di TPA Al Muhajirin Kelurahan Tanjung Aman Lampung Utara - Ica Mustika Sari; Ayunita Ayunita; Paliana Susi Akina; Yudi Surono (Jurnal Kabar Masyarakat, 2024)
In the era of globalization, religious education, especially instilling a love of the Koran in young children, is very important. Al Muhajirin TPA in Tanjung Aman Subdistrict is one of the community service places that focuses on this effort. This activity involved students from the Islamic Religious Education Department from STAI Ibnu Rushd, with the aim of increasing public awareness of religious education and forming Islamic character in children. The methods used include training, mentoring and teaching with a fun approach so that children are more enthusiastic in learning. The results of the service show that the children show interest and enthusiasm in learning the Al-Quran, are able to read correctly according to the rules of tajwid, and understand and practice religious values ​​in everyday life. Through this program, it is hoped that there will be increased awareness of parents and the community regarding the importance of religious education, so that future generations can grow into individuals who love the Koran and have noble morals. This activity also provides recommendations for implementing further programs to strengthen children's love of the Koran.